2013
DOI: 10.1039/c3ra41002a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and utilization of multi-functional magnetic-fluorescent composites for bio-imaging and magnetic hyperthermia therapy

Abstract: This paper describes the synthesis, characterization, and utilization of unique multi-functional magnetic composites that integrate optical and magnetic properties in a single structure for use in hyperthermia therapy, and magnetic and fluorescence imaging. The composites are comprised of nanoscale magnetic core particles that are encapsulated by a silica layer that contains covalently-embedded organic dyes. The morphologies of the nanocomposite particles were characterized by TEM and FE-SEM. Their optical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…A coating of silica (SiO 2 ) can transform a MNP by reducing problems associated with biocompatibility and offering the capacity to functionalize the surface of these nanomagnets [19]. Larumbe et al evaluated the effect of SiO 2 coating on Fe 3 O 4 MNPs and found a reduced Ms and a lower coercivity, hence a lower specific absorption rate (SAR) for SiO 2 -coated Fe 3 O 4 MNPs as compared to analogous uncoated Fe 3 O 4 nanoparticles [21].…”
Section: Effect Of Different Parameters On Magnetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A coating of silica (SiO 2 ) can transform a MNP by reducing problems associated with biocompatibility and offering the capacity to functionalize the surface of these nanomagnets [19]. Larumbe et al evaluated the effect of SiO 2 coating on Fe 3 O 4 MNPs and found a reduced Ms and a lower coercivity, hence a lower specific absorption rate (SAR) for SiO 2 -coated Fe 3 O 4 MNPs as compared to analogous uncoated Fe 3 O 4 nanoparticles [21].…”
Section: Effect Of Different Parameters On Magnetic Propertiesmentioning
confidence: 99%
“…For implantable biosensors such as glucose monitoring systems, biocompatibility has been a significant challenge. These concerns also exist for the various magnetic materials used in research and have frequently been addressed by encapsulating the MNP in an appropriate coating [19]. The nature of the coating is an important consideration in such shell-core MNP designs since the coating might enhance or significantly reduce the magnetic properties of the core based on the interaction between the ligand and the nanoparticle surface [7], the relative thickness of the shell, and the size of the nanoparticle being coated [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic nanoparticles are of interest due to their potential for use in a wide range of important technological applications such as magnetic recording media, 1-4 magnetoelectronic devices, 5-7 ferrouids, 8,9 nanomedicine, [10][11][12][13][14][15][16] and so magnetic materials for magnetic sensors. [17][18][19] Magnetic nanoparticle composites in a nonmagnetic polymer matrix have also become important due to the continued demand associated with the development of biomedical applications, [10][11][12][13]16,20,21 high-density storage materials., [1][2][3]22 and mechanical reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…14,[27][28][29][30] Methods for large-scale synthesis of monodisperse Fe 3 O 4 nanoparticles are also well developed. 14,[27][28][29][30] Methods for large-scale synthesis of monodisperse Fe 3 O 4 nanoparticles are also well developed.…”
Section: Introductionmentioning
confidence: 99%
“…1-4 25 For instance, nano/microcomposites with both fluorescent and magnetic properties can be used in a wide range of applications in biological systems, such as controllable drug release 5 , bioimaging 6,7 , diagnostic and therapeutics 7 . Electrical conduction-magnetism functionalized micro/nanostructures are of 30 special interest due to their potential applications in areas such as electromagnetic interference shielding 8 , microwave absorption 9 and biomedicine 10 .…”
Section: Introductionmentioning
confidence: 99%